ANALISIS PENANGANAN MUATAN PROPANE (C3H8) DAN BUTANE (C4H10) DALAM UPAYA MEMINIMALKAN TERJADINYA VENTING DI KAPAL FULLY LPG/C PRIMA LAUTAN II - Gea Nurul Krisrina; Rizal Rochmansyah; Bayu Yudho Baskoro; Elfira Wirza; Edi Kurniawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Handling Liquefied Petroleum Gas (LPG) cargo on fully refrigerated LPG carriers requires precise control of pressure and temperature to ensure operational safety and prevent venting. Venting is the release of gas vapor into the atmosphere when tank pressure exceeds operational limits, potentially leading to cargo loss, environmental pollution, and increased safety risks. This study aims to analyze the handling of propane and butane cargo, the factors causing venting, and prevention measures on the LPG carrier Prima Lautan II.